Effects of Combined Coconut Shell and Pistachio Shell as Filler and Frictional Additive on the Properties of Particulate Type of Green Friction Composites - Hanmant Virbhadra SHETE; Prashant S. JADHAV (Engineering Transactions, 2024)
Nowadays, cost effectiveness and environment friendliness are crucial requirements for any frictional material along with good frictional stability. Conventional filler materials, such as fly ash, are harmful and create pollution. In contrast, coconut shell and pistachio shell are inexpensive, abundant and green materials, which are otherwise considered agricultural waste. Coconut shell has good heat resistance but poor friction resistance, whereas pistachio shell has good abrasion resistance but poor thermal stability and mechanical properties. Therefore, this study presents the use of a firsthand blend of coconut shell and pistachio shell as cost-effectivefiller and frictional additive to develop a green frictional composite material. The material samples are prepared and tested for physical, mechanical and tribological properties using different blends of coconut shell-pistachio shell powder and binder. The developed friction composites show low water and oil absorption, high flame resistance, thermal conductivity, hardness, higher wear resistance and improved coefficient of friction (COF) for lower amounts of coconut shell and pistachio shell. As the developed frictional composites use natural waste (25% to 35%) instead of fly ash or other pollutant ingredients, they contribute to minimizing pollution and waste disposal problems.